ERRATUM. Update on successful nesting of bearded vulture (Gypaetus barbatus) in the Lanzo Valleys, Piedmont region (NW Italy) - Maurizio Chiereghin; Alessandro Prezzi; Fabiano Sartirana (Rivista Italiana di Ornitologia - Research in Ornithology, 2024)
This erratum corrects the article published in Research in Ornithology, 93 (2): 57-60, 2023 (DOI: 10.4081/rio.2023.690).